Proses Pelaksanaan Pembelajaran Pendidikan Jasmani Adaptif Pada Anak Tuna Grahita Di SLB Negeri Banda Aceh - Afrizal Afrizal; Saddam Hasrul; Azizil Fikri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to find out how the process of learning physical education for mentally retarded children at SLB in Langsa City. This study uses a qualitative descriptive method with survey techniques. Sources of data in this study were students and teachers of SLB Langsa City. Students used as research objects were students of class VII-VIII SLB Langsayang City, all of whom totaled 19 students and physical education teachers from SLB Langsayang City, totaling 2 teachers. Data collection techniques using questionnaires, documentation and interviews. The data analysis technique used was a descriptive analysis model based on qualitative analysis. Based on the results of the study, it was concluded that the physical education learning process for mentally retarded children at SLB Langsa City was going very well. In learning the objective factors of physical education for mentally retarded children have reached a very good level, the material factors for physical education for mentally retarded children show good levels, the attitude and motivational factors of students show very good conditions, the teacher competency factor shows that teachers who teach physical education are adaptive for mentally retarded children SLB Kota Langsa has good competence, physical education infrastructure and facilities factors show adequate conditions, physical education evaluation factors are carried out properly. Keywords: Process, Implementation, Learning